The Clinical Relevance of the Cervical Disc Prosthesis: Combining Clinical Results of Two RCTs. Issue 1 (1st January 2022) - Goedmakers, Caroline M.W.; Bartels, Ronald H.M.A.; Donk, Roland D.; Arts, Mark P.; van Zwet, Erik W.; Vleggeert-Lankamp, Carmen L.A.
Abstract : Study Design: Retrospective analysis was performed on data from 251 patients that were included in two randomized, double-blinded clinical trials comparing clinical results of anterior cervical discectomy and arthroplasty (ACDA) to anterior cervical discectomy and fusion (ACDF), and anterior cervical discectomy (ACD), for single-level disc herniation. Objective: This study aimed to investigate whether the ACDA procedure offers superior clinical results 2 years after surgery, to either ACDF or ACD without instrumentation, in the entire group of patients or in a particular subgroup of patients. Summary of Background Data: The cervical disc prosthesis was introduced to provide superior clinical outcomes after ACD. Methods: Neck Disability Index (NDI), and subscales of the 36-item short-form health survey (SF-36) and McGill pain score were collected at baseline, 1 year and 2 years after surgery. Reoperations and complications were also evaluated. A preliminary subgroup analysis was performed for age, disc height, body mass index (BMI), smoking, and sex. Results: The NDI decreased comparably in all treatment arms to circa 50% of the baseline value and marginal mean NDI differences varied from 0.4 to 1.1 on a 100 point NDI scale, with confidence intervals never exceeding the 20-point minimal clinical important difference (MCID). Secondary outcome parameters showed comparable results. Preliminary subgroup analysis could not demonstrate clinically relevant differences in NDI between treatments after 2 years. Conclusion: After combining data from two Randomized Controlled Trials it can be concluded that there is no clinical benefit for ACDA, when compared with ACDF or ACD 2 years after surgery. Preliminary subgroup analysis indicated outcomes were similar between treatment groups, and that no subgroup could be appointed that benefited more from either ACD, ACDF, or ACDA. Level of Evidence: 1 Abstract : Small differences in NDI with narrow confidence intervals found in this study demonstrate an absence of clinical benefit for ACDA, when compared to ACDF or ACD two years after surgery. Neither for the entire group of patients, nor a subset of patients. Mean NDI differences varied from 0.4 to 1.1 out of 100.